Faktor Yang Mempengaruhi Rawat Inap Berulang Pasien JKN di FKRTL Kantor Cabang Semarang Tahun 2021 - Anisa Hidayah; Diah Ayu Puspandari; Yulita Hendrartini (BPJS Kesehatan, 2022)
Repeated hospitalization is one of the performance indicators of global budget payments. Unplanned repeated hospitalization is a preventable event and its interval is influenced by several factors including the patients, the patients’ clinical condition, and the policy. This research is aimed at analyzing the effect of disease severity, Length of Stay (LOS), and patient discharge status on the repeated hospitalization interval among JKN patients at hospitals BPJS Kesehatan Semarang Branch Office in 2021. This study contributes to the claim management literature by focusing on repeated hospitalization as an evaluation tool to improve the quality of inpatient care. This research was a quantitative study with a cross-sectional design involving hospitalized patients returning for hospitalization within 30 days. Patients who were discharged being referred to other health facilities and those with transplantation, delivery, physiotherapy, and chronic diseases were excluded. Univariate and bivariate analyzes were then performed using the STATA software. The majority of repeated hospitalized patients were aged 12-25 years (69.47%), women (53.88%), and found in type C hospitals (32.85%). There was an association between disease severity and LOS with the repeated hospitalization interval. Increasing severity of illness was found to show a higher risk of repeated hospitalization < 12 days (OR=1.23). Patients with LOS ≥ 4 days increased the risk of repeated hospitalization < 12 days (OR = 1.33). There was no association between discharge status with repeated hospitalization. Conclusion: There is a significant association between disease severity and LOS with repeated hospitalization interval.